Linoleic Acid-Induced Ultra-Weak Photon Emission from Chlamydomonas reinhardtii as a Tool for Monitoring of Lipid Peroxidation in the Cell Membranes - Prasad, Ankush (Public Library of Science, 2011)
Reactive oxygen species formed as a response to various abiotic and biotic stresses cause an oxidative damage of cellular component such are lipids, proteins and nucleic acids. Lipid peroxidation is considered as one of the major processes responsible for the oxidative damage of the polyunsaturated fatty acid in the cell membranes. Various methods such as a loss of polyunsaturated fatty acids, amount of the primary and the secondary products are used to monitor the level of lipid peroxidation. To investigate the use of ultra-weak photon emission as a non-invasive tool for monitoring of lipid peroxidation, the involvement of lipid peroxidation in ultra-weak photon emission was studied in the unicellular green alga Chlamydomonas reinhardtii. Lipid peroxidation initiated by addition of exogenous linoleic acid to the cells was monitored by ultra-weak photon emission measured with the employment of highly sensitive charged couple device camera and photomultiplier tube. It was found that the addition of linoleic acid to the cells significantly increased the ultra-weak photon emission that correlates with the accumulation of lipid peroxidation product as measured using thiobarbituric acid assay. Scavenging of hydroxyl radical by mannitol, inhibition of intrinsic lipoxygenase by catechol and removal of molecular oxygen considerably suppressed ultra-weak photon emission measured after the addition of linoleic acid. The photon emission dominated at the red region of the spectrum with emission maximum at 680 nm. These observations reveal that the oxidation of linoleic acid by hydroxyl radical and intrinsic lipoxygenase results in the ultra-weak photon emission. Electronically excited species such as excited triplet carbonyls are the likely candidates for the primary excited species formed during the lipid peroxidation, whereas chlorophylls are the final emitters of photons. We propose here that the ultra-weak photon emission can be used as a non-invasive tool for the detection of lipid peroxidation in the cell membranes.